Mr. Pink-Whistle$1 (Bs Partys - Blyton, Enid. (George Newnes, London, 1955)
Mr Pink-Whistle is a little fat man with pointed brownie ears and large green eyes; but really he is neither human nor brownie. Until Mr Pink-Whistle decided to use his special talent of making himself invisible, his only friend was his cat, Sooty. But things have now changed
Keywords: Social -- Comedy